Sistem Pendukung Pengambilan Keputusan Penerimaan Beras Untuk Keluarga Miskin (Raskin) Di Kelurahan Sondakan Kecamatan Laweyan Kota Surakarta - Kusmiati, Wawan Laksito YS, Tri Irawati (Jurnal Ilmiah SINUS, 2012)
The purpose of submitting this research paper as a partial fulfillment of the requirements for getting  bachelor degree on the STMIK Sinar Nusantara, also aims to facilitate the process of determing the recipients raskin in the Sondakan. The method of collecting data used by the author in the preparation of this paper is an interview with the KASI   of community development and feasibility assessment methods related  to the recipient rice requirements raskin recipient. In  the  “Decision Support System Acceptance Raskin” author provides  a range calculation  process based on  the economic circumstances, the admissions  raskin  process  based on  the  range value. the results of this study stated that to get "Raskin" must meet 11 criteria set by the government.  This system is made with the programming language Borland Delphi 7  and uses a MySQL database.  Keywords: Decision Support System Acceptance